2010
DOI: 10.1128/jvi.02715-09
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an Infectious Endogenous Retrovirus in a Proportion of Live Attenuated Vaccines for Pets

Abstract: The genomes of all animal species are colonized by endogenous retroviruses (ERVs). Although most ERVs have accumulated defects that render them incapable of replication, fully infectious ERVs have been identified in various mammals. In this study, we isolated a feline infectious ERV (RD-114) in a proportion of live attenuated vaccines for pets. Isolation of RD-114 was made in two independent laboratories using different detection strategies and using vaccines for both cats and dogs commercially available in Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…In Japan, feline cell lines are widely used to produce vaccines for dogs, particularly against canine parvovirus. The level of infectious RD-114 virus found in canine virus vaccines has been reported to be as high as 1,800 TCID 50 /ml (3). In earlier work, we confirmed the contamination of canine vaccines with the infectious RD-114 virus (4).…”
supporting
confidence: 73%
“…In Japan, feline cell lines are widely used to produce vaccines for dogs, particularly against canine parvovirus. The level of infectious RD-114 virus found in canine virus vaccines has been reported to be as high as 1,800 TCID 50 /ml (3). In earlier work, we confirmed the contamination of canine vaccines with the infectious RD-114 virus (4).…”
supporting
confidence: 73%
“…RD-114 has been reported to be produced as infectious viruses in some feline cell lines and to be present as a contaminant in a proportion of live attenuated vaccines for pets [21]. It is very difficult to completely exclude the proviral DNA of RD-114 from cells, as endogenous retroviruses are usually integrated into multiple loci of the host chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Many live attenuated vaccines for dogs and cats are produced using feline cell lines, such as Crandell-Rees feline kidney (CRFK) cells which produce RD-114 virus [2,8,14]. We previously reported that a proportion of canine and feline live attenuated vaccines produced using feline cell lines was in fact contaminated with infectious RD-114 virus [4]. The National Veterinary Assay Laboratory, (Kokubunji, Tokyo, Japan) also confirmed this incidence independently [7].…”
mentioning
confidence: 82%